(untitled) (European Journal of Pure and Applied Mathematics, 2024)
A prime labeling of a graph G is a map from the vertex set of G to the set 1, 2, ..., |V (G)| such that any two adjacent vertices in the graph G have labels that are relatively prime. In this paper, we discuss when the disjoint union of some graphs is a prime graph.